The effect of attenuation map, scatter energy window width, and volume of interest on the calibration factor calculation in quantitative 177Lu SPECT imaging: Simulation and phantom study. (December 2018) - Karimi Ghodoosi, Elham; D'Alessandria, Calogero; Li, Ye; Bartel, Alexandra; Köhner, Markus; Höllriegl, Vera; Navab, Nassir; Eiber, Matthias; Li, Wei Bo; Frey, Eric; Ziegler, Sibylle
Highlights: Dependency of 177 Lu SPECT calibration factors on phantom size. Influence of volume of interests on 177 Lu SPECT calibration factors. Effect of attenuation maps on 177 Lu SPECT calibration factor. ESSE performed better than TEW in simulations. Scatter energy windows are suggested for improved TEW scatter correction. Abstract: Purpose: The objective of this study was to evaluate the image degrading factors in quantitative 177 Lu SPECT imaging when using both main gamma photopeak energies. Methods: Phantom measurements with two different vials containing various calibrated activities in air or water were performed to derive a mean calibration factor (CF) for large and small volumes of interest (VOIs). In addition, Monte Carlo simulations were utilized to investigate the effect of scatter energy window width, scatter correction method, such as effective scatter source estimation (ESSE) and triple energy window (TEW), and attenuation map on the quantification of 177 Lu. Results: The measured mean CF using large and small VOIs in water was 4.50 ± 0.80 and 4.80 ± 0.72 cps MBq −1, respectively. Simulations showed a reference CF of 3.3 cps MBq −1 for the water-filled phantom considering all photons excluding scattered events. By using the attenuation map generated for 190 keV photons, the calculated CFs for 113 keV and 208 keV are 10% lower than by using the weighted mean energy of 175 keV for 177 Lu. The calculated CF using the TEW correction was 17% higher than using the ESSE method for a water-filled phantom. However, our findings showed that an appropriate scatter window combination can reduce this difference between TEW and ESSE methods. Conclusions: The present work implies that choosing a suitable width of scatter energy windows can reduce uncertainties in radioactivity quantification. It is suggested to generate the attenuation map at 113 keV and 208 keV, separately. Furthermore, using small VOIs is suggested in CF calculation.